2012
DOI: 10.1002/pds.2262
|View full text |Cite
|
Sign up to set email alerts
|

Initial and subsequent therapy for newly diagnosed type 2 diabetes patients treated in primary care using data from a vendor‐based electronic health record

Abstract: Clinical and demographic characteristics influence choice and duration of initial oral hypoglycemic treatment as well as regimen changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
7
17
0
3
Order By: Relevance
“…Black patients have been demonstrated to have lower rates of health literacy [57], which is a demonstrated risk factor for hypoglycemia [60]. In addition, race may impact a clinician's choice of diabetes agents and changes in regimens [61]. In the pediatric population, minority children were shown to be less likely than white children to receive diabetes management support in school [62].…”
Section: Discussionmentioning
confidence: 99%
“…Black patients have been demonstrated to have lower rates of health literacy [57], which is a demonstrated risk factor for hypoglycemia [60]. In addition, race may impact a clinician's choice of diabetes agents and changes in regimens [61]. In the pediatric population, minority children were shown to be less likely than white children to receive diabetes management support in school [62].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of prescription patterns in primary care show that the majority of newly diagnosed patients with type 2 diabetes are treated with metformin monotherapy 9. Higher HbA1c levels are associated with increased likelihood of being prescribed combination therapy, perhaps reflecting recommendations from expert groups that initial combination therapy (rather than stepwise addition of agents) should be considered for patients unlikely to achieve control with monotherapy 1,10.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nearly one‐quarter (23%) of newly diagnosed T2DM patients in the US had an HbA1c ≥9.0% prior to initiation of treatment . For such patients, initiating insulin is difficult, although it has been almost 10 years since the ACE/AACE Diabetes Road Map suggested insulin therapy for treatment‐naïve patients with high HbA1c .…”
Section: List Of Pros and Cons Of Short‐term Intensive Insulin Theramentioning
confidence: 99%